Bone turnover markers and bone mineral density in patients with type 2 diabetes - AKALIN, Aysen; YORULMAZ, Göknur; ALATAŞ, İ. Özkan; ONBAŞI, Kevser; EFE, Fatma Belgin (The European research journal, 2023)
Background: This study was designed in order to evaluate bone and mineral metabolism in type 2 diabetic patients and its relationship with bone mineral density and diabetic microvascular complications. Methods: Forty two type 2 diabetic patients and 23 healthy cases were included in the study. Serum osteocalcin, procollagen type 1 – C peptide (PICP), total and bone specific alkaline phosphatase (bone ALP), urinary deoxypyridinoline (free DPD), parathormone (PTH), serum and urinary calcium and phosphorus levels were measured. Bone mineral densities of all subjects were studied in lumbar vertebra and femur region using dual X-ray absorptiometry (DXA). Results: Serum osteocalcin and bone ALP levels of the diabetics were found to be significantly lower and total alkaline phosphatase and calcium levels were higher in diabetic patients compared to healthy controls, but PICP and free DPD levels were not different between these two groups. There was a positive correlation between PTH levels and urinary DPD excretion. Among diabetics, serum osteocalcin levels increased with the impairment of renal functions. Bone mineral densities were lower in diabetics with worse renal functions. Conclusion: Bone turnover is slow in type 2 diabetes and there is no prominent bone loss related to this condition. PTH is an important factor determining the rate of bone resorption in diabetics. Renal functional impairment is the most important factor affecting the bone mass in type 2 diabetic patients.